Students’ Experience of Service Quality of Technical Vocational Education and Training (TVET) Programs in Philiphines’s Private Higher Educational Institutions (HEIs) - Tadle, Rene Luis; Valdez, Les Paul; Fernandez, Ronald; Uy, Chin; de Castro, Belinda (Journal of Technical Education and Training, 2021)
This study aimed to describe students' experience of service quality (training quality and delivery, student support, training facilities and student services) while enrolled in various private HEI-TVET programs. Further, it sought to determine if there were differences in the perception of students of the same service quality across work experience, certification, high school curriculum, and availability of scholarship.  Following review of TVET literature a multi-aspect questionnaire was developed. Students (n=234) enrolled in various technical vocational courses in private HEIs participated in this study. The data was analyzed using independent t-test for comparisons across demographic profiles while Pearson's r was utilized to test relationships between variables. Results showed high overall satisfaction on the quality of TVET training of private HEIs. The study found that work experience, certification, high school curriculum, and scholarship make a significant difference in the students' perception in some of the quality indicators of private HEIs TVET courses. The findings are deemed valuable and useful for school and program managers, policy makers and researchers in the training and educational sector.